2011
DOI: 10.1111/j.1440-1827.2011.02704.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal thrombotic microangiopathy associated with chronic graft‐versus‐host disease after allogeneic hematopoietic stem cell transplantation

Abstract: Thrombotic microangiopathy (TMA) is a major complication after hematopoietic stem cell transplantation (HSCT). In this study, we examined the clinical and pathologic features of 2 patients and 5 autopsy cases with HSCT-associated renal TMA to clarify the association between graft-versus-host disease (GVHD) and renal TMA. The median interval between HSCT and renal biopsy or autopsy was 7 months (range 3-42 months). Clinically, acute and chronic GVHD occurred in 7 and 4 patients, respectively. Clinical evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
59
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 42 publications
6
59
1
Order By: Relevance
“…23,38,40 In their study of 26 autopsy cases, El-Seisi et al 38 noted substantial interstitial fibrosis, as we found in our group, but they also found tubulitis of unspecified degree in 67% of autopsied hematopoietic cell transplant patients, although they did not find an association of tubulitis with clinical GVHD. In a study of seven hematopoietic cell transplant patients with thrombotic microangiopathy, Mii et al 23 noted mild or moderate interstitial inflammation in all patients (two biopsy, five autopsy).…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…23,38,40 In their study of 26 autopsy cases, El-Seisi et al 38 noted substantial interstitial fibrosis, as we found in our group, but they also found tubulitis of unspecified degree in 67% of autopsied hematopoietic cell transplant patients, although they did not find an association of tubulitis with clinical GVHD. In a study of seven hematopoietic cell transplant patients with thrombotic microangiopathy, Mii et al 23 noted mild or moderate interstitial inflammation in all patients (two biopsy, five autopsy).…”
Section: Discussionsupporting
confidence: 59%
“…In separate studies, Mii et al, 23,49 Laskin et al, 25 and Sakamoto et al 50 demonstrated C4d labeling in arterioles and glomeruli of biopsy and autopsy kidney specimens from patients with hematopoietic cell transplant and thrombotic microangiopathy. Mii et al 23,49 surmised that this finding might provide evidence of antibodymediated pathology, based on analogy with antibody mediation rejection in solid organ transplantation. 49 Subsequently, Laskin et al 25 found arteriolar but not glomerular C4d staining to correlate with histologic thrombotic microangiopathy in patients with both allogeneic and autologous hematopoietic cell transplant.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…According to kidney histological findings, glomeruli accompanied with diffuse double contour in glomerular basement membrane, thickening of vascular intima, and substantial width of subendothelial widening was observed. Moreover, C4d staining was detected in a part of glomerular capillaries and peritubular capillaries, which coincides with the symptoms of GVHD [8]. We speculated that TMA was improved by increase of tacrolimus with improvement of GVHD.…”
Section: Discussionmentioning
confidence: 60%